2009
DOI: 10.3390/v1030818
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis Delta Virus RNA Replication

Abstract: Hepatitis delta virus (HDV) is a distant relative of plant viroids in the animal world. Similar to plant viroids, HDV replicates its circular RNA genome using a double rolling-circle mechanism. Nevertheless, the production of hepatitis delta antigen (HDAg), which is indispensible for HDV replication, is a unique feature distinct from plant viroids, which do not encode any protein. Here the HDV RNA replication cycle is reviewed, with emphasis on the function of HDAg in modulating RNA replication and the nature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
75
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 74 publications
0
75
0
1
Order By: Relevance
“…8 Notably, there is also a general consensus involving Pol II in replication of HDV but, while some studies implicate this enzyme in the nucleoplasmic synthesis of genomic and antigenomic strands (in addition to the subgenomic mRNA of antigenomic sense encoding ∂Ag), others indicate that elongation of antigenomic strands is catalyzed by Pol I in the nucleolus; to complicate even more the situation, new data have additionally implicated Pol III. Evidence supporting these partially contradictory views, as well as the experimental approaches on which they are based, can be found in the original publications and in recent reviews in reference [41][42][43]. Crystallographic analysis has shown that an RNA templateproduct duplex occupies in Pol II the same site as the DNA-RNA was coined, while the linear form is predominantly encapsidated in viroid-like satellite RNAs of nepo-and luteoviruses.…”
Section: Polymerization Of Rna Strandsmentioning
confidence: 94%
See 2 more Smart Citations
“…8 Notably, there is also a general consensus involving Pol II in replication of HDV but, while some studies implicate this enzyme in the nucleoplasmic synthesis of genomic and antigenomic strands (in addition to the subgenomic mRNA of antigenomic sense encoding ∂Ag), others indicate that elongation of antigenomic strands is catalyzed by Pol I in the nucleolus; to complicate even more the situation, new data have additionally implicated Pol III. Evidence supporting these partially contradictory views, as well as the experimental approaches on which they are based, can be found in the original publications and in recent reviews in reference [41][42][43]. Crystallographic analysis has shown that an RNA templateproduct duplex occupies in Pol II the same site as the DNA-RNA was coined, while the linear form is predominantly encapsidated in viroid-like satellite RNAs of nepo-and luteoviruses.…”
Section: Polymerization Of Rna Strandsmentioning
confidence: 94%
“…A final related issue, still controversial, is whether synthesis of the subgenomic ∂Ag-mRNA is linked to the HDV replication, or the processes are independent and reside in distinct complexes. 42 This complication does not exist in viroids and viroid-like satellite RNAs, which do not encode any protein in their genomes and, therefore, there is no possible interference between replication and transcription.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, this protein aids transcription of both DNA and RNA templates by a DdRP, though the mechanism by which it accomplishes a switch in substrate specificity remains unclear. HDV encodes two proteins, small and large delta antigens (HDAg-S and HDAg-L) that are involved in HDV transcription/replication and packaging, respectively (Tseng and Lai, 2009). HDAg-L is encoded by a read-through of mRNA encoding the HDAg-S, thereby differing from the latter by having 19 extra amino acids in the C terminus.…”
Section: Discussionmentioning
confidence: 99%
“…The circular HDV RNA genome is the smallest known to infect humans and is replicated by host RNA polymerase (8). Replication occurs through a double-rolling-circle mechanism that involves the circular reverse complement of the genome, the antigenome (9,10). For both of these circular RNAs, one-half exhibits substantial sequence complementarity to the other half, such that they collapse into linear closed hairpin structures in which short (2 to 10 nucleotides [nt]) base-paired segments are interspersed with small bulges and internal loops but no branches (11,12).…”
mentioning
confidence: 99%